Target genes, variants, tissues and transcriptional pathways influencing human serum urate levels - Tin, Adrienne; Marten, Jonathan; Halperin Kuhns, Victoria L; Li, Yong; Wuttke, Matthias; Kirsten, Holger; Sieber, Karsten B; Qiu, Chengxiang; Gorski, Mathias; Yu, Zhi; Giri, Ayush; Sveinbjornsson, Gardar; et al. (Nature genetics, 2019)
Elevated serum urate levels cause gout and correlate with cardiometabolic diseases via poorly understood mechanisms. We performed a trans-ancestry genome-wide association study of serum urate in 457,690 individuals, identifying 183 loci (147 previously unknown) that improve the prediction of gout in an independent cohort of 334,880 individuals. Serum urate showed significant genetic correlations with many cardiometabolic traits, with genetic causality analyses supporting a substantial role for pleiotropy. Enrichment analysis, fine-mapping of urate-associated loci and colocalization with gene expression in 47 tissues implicated the kidney and liver as the main target organs and prioritized potentially causal genes and variants, including the transcriptional master regulators in the liver and kidney, HNF1A and HNF4A. Experimental validation showed that HNF4A transactivated the promoter of ABCG2, encoding a major urate transporter, in kidney cells, and that HNF4A p.Thr139Ile is a functional variant. Transcriptional coregulation within and across organs may be a general mechanism underlying the observed pleiotropy between urate and cardiometabolic traits.
Keywords: Genetic Loci; nádorové proteiny; Gout; kohortové studie; kyselina močová; genetické lokusy; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-alpha; Cohort Studies; Organ Specificity; signální transdukce; ATP Binding Cassette Transporter, Subfamily G, Member 2; Genetic Markers; Kidney; Genome-Wide Association Study; hepatocytární jaderný faktor 1-alfa; jednonukleotidový polymorfismus; Uric Acid; metabolické nemoci; Signal Transduction; Metabolic Diseases; genetické markery; kardiovaskulární nemoci; Polymorphism, Single Nucleotide; lidé; játra; ABC transportér z rodiny G, člen 2; ledviny; Humans; Hepatocyte Nuclear Factor 4; dna (nemoc); Neoplasm Proteins; Cardiovascular Diseases; Liver; hepatocytární jaderný faktor 4; orgánová specificita; genetická predispozice k nemoci; celogenomová asociační studie